Encuadre de un modelo alternativo para el estudio de la calidad universitaria. Una propuesta para psicología - Orellana Manrique, Oswaldo (2005)
Present is an exploratory investigation on the university quality. It realizes a historical review on the functions of the university and a contemporary review brings over of the concept of university quality, Debating his content and extension, principally in his application in the Peru. It approaches the models got in Latin America and his manifestations in psychologists’ formation, Centring on the National Major University of San Marcos And concluding with the offer of topics to evaluate the quality from a model for the autoevaluation.